Knowledge, Use, and Perceived Value of University Student Services: International and Domestic Student Perceptions - Perry, Cody J.; Lausch, David; McKim, Courtney A; Weatherford, Jennifer (Journal of International Students, 2020)
Universities throughout the United States struggle with fiscal issues that can be improved by greater retention and graduation rates. One step often taken is to cut student service spending, which hurts students’ ability to finish a degree. While some have advocated for greater spending in student services, we contend that current services may suffice. Since many students do not understand the services available, many do not take advantage of university offerings. This study looks at differences in perceptions between international and domestic students concerning awareness, use, and value of services available at a western U.S. land-grant university. We found many students, both international and domestic, are not aware of available programs, which correlates to less use and perceived value of these services and programs.